Types of Holography in Artistic Practices - Arslan, Merve; Sürmeli, Kader (Universitas Komputer Indonesia, 2025)
Art, beyond being an aesthetic form of expression, offers new experiential possibilities shaped by technological advances. In this context, the integration of holographic elements into artworks has introduced new visual and conceptual dimensions. This study explores how holography-defined as the technique of creating three-dimensional images using the interference and diffraction of light-functions within artistic practices. Although there are approximately sixty types of holography, only a few are suitable for art. The research focuses on three primary types: reflection, transmission, and hybrid holography. Reflection holography produces images by reflecting light off a surface, creating depth and realism depending on light placement and viewer position. Transmission holography allows light to pass through the hologram, offering a different spatial perception. Hybrid holography combines different techniques or technologies, often utilizing digital algorithms to produce images without physical objects. These types allow artists to redefine the relationship between artwork and viewer, enhancing interactive and immersive experiences. This study, conducted using qualitative research methods, aims to provide a comprehensive understanding of holography's development and application in the arts from the 1960s to the present. Through selected examples, it examines the technical characteristics, visual effects, and viewer engagement offered by each holography type. Keywords: Types of Holography, Holographic Art, Art Practices